A 0.28 THz Power-Generation and Beam-Steering Array in CMOS Based on Distributed Active Radiators - Sengupta, K.; Hajimiri, A. (IEEE journal of solid-state circuits, 2012)
In this paper, we present a scalable transmitter architecture for power generation and beam-steering at THz frequencies using a centralized frequency reference, sub-harmonic signal distribution, and local phase control. The power generation and radiator core is based on a novel method called distributed active radiation, which enables high conversion efficiency from DC to radiated terahertz power above f max of a technology. The design evolution of the distributed active radiator (DAR) follows from an inverse design approach, where metal surface currents at different harmonics are formulated in the silicon chip for the desired electromagnetic field profiles. Circuits and passives are then designed conjointly to synthesize and control the surface currents. The DAR consists of a self-oscillating active electromagnetic structure, comprising of two loops which sustain out-of-phase currents at the fundamental frequency and in-phase currents at the second harmonic. The fundamental signal, thus gets, spatially filtered, while the second harmonic is radiated selectively, thereby consolidating signal generation, frequency multiplication, radiation of desired harmonic and filtration of undesired harmonics simultaneously in a small silicon footprint. A two-dimensional 4×4 radiating array implemented in 45 nm SOI CMOS (without high-resistivity substrate) radiates with an EIRP of +9.4 dBm at 0.28 THz and beam-steers in 2D over 80° in both azimuth and elevation. The chip occupies 2.7 mm × 2.7 mm and dissipates 820 mW of DC power. To the best of the authors' knowledge, this is the first reported integrated beam-scanning array at THz frequencies in silicon.